(untitled) (The Pakistan Development Review, 1992)
This paper provides estimates of the level of inequality in the distribution of land and other irrigation-related land variables among agricultural households, across farm size groups both at the national and provincial levels, at a point in time as well as over a period of time; it decomposes the levels of inequality in terms of its two components, namely, "within province" and "between provinces" inequality; and it estimates the relative performance of the four provinces in achieving equity in irrigation distribution. In doing this analysis, the paper makes use of the agricultural census reports pertaining to the years 1959-60, 1971-1972, and 1979-1980. The paper’s major results are that there exists considerable intra- and interprovincial inequality in Pakistan. Of the two major contributors to the overall inequality in the country as a whole, the withinprovince inequality component contributes more than 90 percent of the total inequality. The paper identifies the two main reasons for the high within-province inequality as being (I) the very highly skewed distribution of land across cultivating households and (2) the lack of regressi vity in the distribution of irrigation across farm size groups, especially that of govemment"controlled canal irrigation. The paper recommends a lexicographic ordering of canal irrigation distribution, under which irrigation water will be provided first to irrigate all the irrigable land of the smallest of farms, and after fulfilling their demands, it will fulfil the demands of the second smallest farm size group, and so on.